Teori Tindak Tutur dalam Studi Pragmatik - Safitri, Rizki Dian; Mulyani, Mimi; Farikah (Kajian Bahasa dan Sastra (KABASTRA), 2021)
This article explains the theory of speech acts proposed by John L. Austin and his student John R. Searle. Speech act theory is a sub-field of pragmatics. This field of study deals with the ways in which words can be used not only to present information but also to carry out actions. This theory considers three levels or components of speech: locutionary acts (the making of a meaningful statement, saying something that a hearer understands), illocutionary acts (saying something with a purpose, such as to inform), and perlocutionary acts (saying something that causes someone to act). Many view speech acts as the central units of communication, with phonological, morphological, syntactic, and semantic properties of an utterance serving as ways of identifying the meaning of a speaker’s utterance or illocutionary force. There are five types of Illocutionary points according to Searle: declarations, assertives, expressives, directives, and commissives (1979:viii). A speech act, in order to be successful, needs to be performed along with certain types of conditions. These conditions were categorized by the linguist John Searle, who introduced the term felicity conditions: propositional content condition, preparatory condition, sincerity condition, and essential condition.